Evaluation of hydrodynamic behavior of biosand filters using computational fluid dynamics combined with the design of experiments. Issue 2 (31st December 2021) - Sala, Dominique Martins; Rezende, Ricardo Vicente de Paula; Lautenschlager, Sandro Rogério
Abstract: Biosand filters (BSFs) are widely used in rural and urban areas where access to drinking water is limited or non-existent. This study applies computational fluid dynamics in the assessment of hydrodynamic characteristics considering changes in the design of two BSF models to make construction options available to communities, without losing hydrodynamic efficiency. The commercial code ANSYS-CFX 20.1 together with a central composite design of experiments methodology to simulate the flow was used under different combinations of porosities, permeabilities, pipe diameters, and filter diameters and heights. These parameters were combined statistically from Statistica 13.3. Our results have shown that combining greater filter depths with smaller pipe diameters has played a key role in the BSF best performance, and the CAWST V10 model has performed better than HydrAid, with lower velocities and longer hydraulic retention times. HIGHLIGHTS: Stable mathematical models predict water flow patterns in biosand filters. The CAWST V10 model promoted more favorable hydrodynamic conditions for microbiological treatment than HydrAid. The performance in water treatment is obtained for different heights and diameters of filters, and different diameters of tubes. Graphical Abstract